2016
DOI: 10.1186/s12879-016-2041-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance and population structure of M.tuberculosis isolates from prisons and communities in Ethiopia

Abstract: BackgroundThe population structure and drug resistance pattern of Mycobacterium tuberculosis complex (MTBC) isolates in Ethiopian prisons and some communities is still unknown.MethodsA comparative cross sectional study was conducted on 126 MTBC strains isolated from prisons and communities in southwestern, southern and eastern Ethiopia. Phenotypic drug susceptibility testing was performed with the MGIT960 system. Combined 24-loci Mycobacterium interspersed repetitive unit-variable number tandem repeat and spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
6
18
0
Order By: Relevance
“…The predominant MTBC lineages in this study were lineage 4 followed by lineage-3; findings that are similar to other studies conducted in Ethiopia [ 17 , 19 , 26 ]. We also demonstrate that local sub-linages such as the newly described “Ethiopia_4” and the closely related Ethiopia_3 (both part of lineage 4 and related to TUR genotype strains) dominate among Ethiopian TB cases but do not play a major role in the global TB epidemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The predominant MTBC lineages in this study were lineage 4 followed by lineage-3; findings that are similar to other studies conducted in Ethiopia [ 17 , 19 , 26 ]. We also demonstrate that local sub-linages such as the newly described “Ethiopia_4” and the closely related Ethiopia_3 (both part of lineage 4 and related to TUR genotype strains) dominate among Ethiopian TB cases but do not play a major role in the global TB epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…rural vs. metropolitan setting) or other demographic differences (e.g. age, gender) [ 26 ]. However, these studies have consistently shown a large proportion of TB cases in Ethiopia are due to recent transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant MTBC lineages in this study were lineage 4 followed by lineage 3; findings that are similar to other studies conducted in Ethiopia [10, 19, 22]. We also demonstrate that local sub-linages such as the newly described “Ethiopia_4” and the closely related to Ethiopia_3 (both part of lineage 4 and related to TUR genotype strains) dominate among Ethiopian TB cases but do not play a major role in the global TB epidemic.…”
Section: Discussionsupporting
confidence: 90%
“…Being aware of the limitations mediated by the small sample size and the cross-sectional sampling scheme, our data suggest that MTBC transmission is still a major public health concern in Eastern Ethiopia and is not limited to congregate living facilities, e.g. universities or prisons [22].…”
Section: Discussionmentioning
confidence: 99%
“…The goals of this study were to calculate the prevalence of self-reported TB diagnosed in all the Peruvian correctional facilities (CFs), and to evaluate its relationship with various demographic and clinical factors registered on a nation-wide survey among prison inmates conducted for the first time in Peru. The importance of this research lies on the pivotal role that people deprived of their liberty played on TB transmission, especially resistant forms [16,17] which are difficult to manage and could result in high mortality rates [18]. Importantly, we have not found previous studies in Peru where its prevalence was calculated at national level, and there are limited efforts investigating factors associated with TB in local prisons.…”
Section: Introductionmentioning
confidence: 99%